House That Jack Built / c.1858-1862 - Adam Matthew Digital (Firm) (Marlborough, Wiltshire : Adam Matthew Digital, New York : McLoughlin Bros, 2020)
"Title, imprint statement, and series transcribed from p. [1] of wrapper. Series transposed from head of wrapper. McLoughlin Bros. was located at 24 Beekman St., New York, between 1858 and 1862. Wrapper printed in red and black ink. Wood engraving, p. [1] of wrapper signed, "E.P.C." (i.e., Edward P. Cogger). "McLoughlin Brothers ... manufacturers of toy books, primers, games for children, abc cards, blocks, &c."--publisher's advertisement, p. [4] of wrapper. Includes ads for paper dolls and paper furniture."
AMDigital Reference:217396
American Antiquarian Society
Keywords: Animals and Nature; Family and Relationships; Nationality and Place; Children's poetry; Picture books for children; Rats; Cats; Dogs; Cows; Girls; Courtship; Marriage; Clergy; Roosters; Children's poetry; Roosters; Clergy; Marriage; Courtship; Girls; Cows; Dogs; Cats; Rats; Picture books for children